Histone Acetyltransferase KAT2A Stabilizes Pluripotency with Control of Transcriptional Heterogeneity. (17th October 2018) - Moris, Naomi; Edri, Shlomit; Seyres, Denis; Kulkarni, Rashmi; Domingues, Ana Filipa; Balayo, Tina; Frontini, Mattia; Pina, Cristina
Abstract : Cell fate transitions in mammalian stem cell systems have often been associated with transcriptional heterogeneity; however, existing data have failed to establish a functional or mechanistic link between the two phenomena. Experiments in unicellular organisms support the notion that transcriptional heterogeneity can be used to facilitate adaptability to environmental changes and have identified conserved chromatin-associated factors that modulate levels of transcriptional noise. Herein, we show destabilization of pluripotency-associated gene regulatory networks through increased transcriptional heterogeneity of mouse embryonic stem cells in which paradigmatic histone acetyl-transferase, and candidate noise modulator, Kat2a (yeast orthologue Gcn5), have been inhibited. Functionally, network destabilization associates with reduced pluripotency and accelerated mesendodermal differentiation, with increased probability of transitions into lineage commitment. Thus, we show evidence of a relationship between transcriptional heterogeneity and cell fate transitions through manipulation of the histone acetylation landscape of mouse embryonic stem cells, suggesting a general principle that could be exploited in other normal and malignant stem cell fate transitions. Abstract : The histone acetyltransferase Kat2a modifies histones by adding acetyl groups that change the dynamics of transcription. Kat2a inhibition increases transcriptional heterogeneity in mouse embryonic stem cells, destabilizes the transcriptional network, and increases the probability of cell fate transitions.